Connecting - Helen Walker; Jim Super; Pamela Hartman; Nancy Myers; Andrea Siegel; Traci L. Merritt; Susan A. Schiller; Wilma Romatz (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
Helen Walker. Connecting. Jim Super—Fearless Pamela Hartman—English? I'd Rather Read A Book Nancy Myers—B Andrea Siegel—Walking the Talk, Breathing the Breath Traci L. Merritt—The Day Jenny Died Susan A. Schiller—Touched by the Spirit in AEPL Topics Wilma Romatz—On the Delicate Art of Teaching